2006
DOI: 10.1158/0008-5472.can-05-3575
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-Negative Histone H3 Lysine 27 Mutant Derepresses Silenced Tumor Suppressor Genes and Reverses the Drug-Resistant Phenotype in Cancer Cells

Abstract: Histone modifications and DNA methylation are epigenetic phenomena that play a critical role in many neoplastic processes, including silencing of tumor suppressor genes. One such histone modification, particularly at H3 and H4, is methylation at specific lysine (K) residues. Whereas histone methylation of H3-K9 has been linked to DNA methylation and aberrant gene silencing in cancer cells, no such studies of H3-K27 have been reported. Here, we generated a stable cell line overexpressing a dominant-negative poi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
80
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 44 publications
8
80
0
Order By: Relevance
“…However, LA is less chemosensitive than other NSCLC. Our findings were consistent with another study showing that loss of EZH2-mediated methylation of histone H3 lysine 27 (H3K27) re-sensitized ovarian cancer cells to cisplatin (25). It was demonstrated that overexpression of EZH2 contributed to acquired cisplatin resistance in ovarian cancer cells in vitro and in vivo (26).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…However, LA is less chemosensitive than other NSCLC. Our findings were consistent with another study showing that loss of EZH2-mediated methylation of histone H3 lysine 27 (H3K27) re-sensitized ovarian cancer cells to cisplatin (25). It was demonstrated that overexpression of EZH2 contributed to acquired cisplatin resistance in ovarian cancer cells in vitro and in vivo (26).…”
supporting
confidence: 93%
“…Our results identified EZH2 as an important factor in LA cell chemoresistance for the first time. Abbosh et al (25) found that H3K27 methylation played an important role in drug resistance. EZH2 deletion sensitized pancreatic cancer cells to doxorubicin and gemcitabine (27), because EZH2 mediated H3K27 methylation is a mark of heterochromatin, and loss of chromatin compaction could allow increased DNA damage at lower doxorubicin and gemcitabine doses leading to a decreased survival in EZH2 deleted pancreatic cancer cells.…”
mentioning
confidence: 99%
“…In ovarian cancer, decreased expression of H3K27me3 is significantly associated with high‐grade and advanced‐stage tumours, but not with the histological type 78, predicting resistance to chemotherapy 79 and a poor clinical outcome in ovarian cancer and other malignancies 78. Removal of H3K27 methylation was shown to lead to re‐expression of the RASSF1 tumour suppressor and resensitize drug‐resistant ovarian cancer cells to cisplatin; this increased platinum access to DNA was likely due to relaxation of condensed chromatin 80. Sirtuin1 (SIRT1) is a nicotinamide adenine dinucleotide‐dependent deacetylase and a class III histone deacetyltransferase.…”
Section: Molecular Portraits Underlying Th Of Eocmentioning
confidence: 99%
“…7 To explore the mechanism of resistance reversal by EZH2 knockdown, we performed western blotting to examine the level of H3K27me3 in EZH2-knockdown A2780/DDP cells. H3K27me3 level in shEZH2-A2780/ DDP cells was decreased by 50.5% compared with untransfected cells (p < 0.001; Knockdown of EZH2 induces G 2 /M cell cycle arrest in ovarian cancer cells.…”
Section: Ezh2 Expression Is Elevated In Drug-resistant Ovarian Cancermentioning
confidence: 99%
“…[4][5][6] Recent data indicate that histone H3 lysine 27 (H3K27) methylation plays a important role in drug resistance, opening a novel insight to decipherering epigenetic mechanisms of tumor chemoresistance. 7 enhancer of Zeste homologue 2 (eZh2), a specific histone 3 lysine 27 (h3K27) methyltransferase, plays a critical role in tumorigenesis and cancer progression through epigenetic gene silencing and chromatin remodeling. however, the role of eZh2 in chemotherapy resistance is unknown.…”
Section: Introductionmentioning
confidence: 99%